A comparison of risk factors for various forms of trauma in the lives of lesbian, gay, bisexual and heterosexual homeless youth. Issue 4 (8th August 2018) - Tyler, Kimberly A.; Schmitz, Rachel M.
ABSTRACT: Numerous homeless youth experience trauma prior to leaving home and while on the street. Bullying and trading sex (i.e. exchanging sexual favors for survival items such as food) are additional forms of trauma experienced by many homeless youth. Although lesbian, gay, and bisexual (LGB) homeless youth experience higher rates of child abuse compared to their heterosexual counterparts, there is a paucity of research comparing these two groups. As such, we compare whether difficulties finding items of necessity (e.g. food) and different forms of trauma including child sexual abuse, being bullied, trading sex, and street sexual victimization significantly differ for LGB and heterosexual homeless youth. Bivariate results reveal that LGB youth have more trouble finding shelter and are more likely to trade sex compared to heterosexual youth. Logistic regression results show that trading sex is correlated with street sexual victimization. In the second model, we find that being female, experiencing more child sexual abuse, and ever having traded sex are all positively linked with street sexual victimization. LGB youth are over-represented among homeless youth populations and are also more likely to trade sex; therefore, these young people need services that are widely accessible and specific to their needs.